Analisis Novel If I Can’t Karya Fiatuzzahro (Kajian Strukturalisme Genetik- Lucien Goldmann) - Tiana, Elsa; Aisah, Aisah; Maulana, Syahrul; Hartati, Dian (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to describe human problems in the novelIf I Can’t by Fiatuzzahro. The theory that researchers use is the theory of genetic structuralism from Lucien Goldmann. The research subject is a novelIf I Can’t by Fiatuzzahro. The approach used in this study is a qualitative approach while the research method used is analytic descriptive method. The data collection technique used in this study is the observing and noting technique. Data analysis techniques, including data reduction, data presentation, and drawing conclusions or verification. The results of the study show that there are 1) Human Facts, 2) collective subject, 3) world view, 4) structure of literary works, 5) dialectic of understanding, 6) explanation and understanding in the novelIf I Can’t by Fiatuzzahro.